2000
DOI: 10.1159/000026641
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Frontal Midline Theta Activity in Patients with Generalized Anxiety Disorder

Abstract: The appearance of frontal midline theta activity (Fmθ), recognized as distinct EEG theta rhythm in the frontal midline area during performance of a mental task, reflects feelings of relief from anxiety in humans. In the present study, EEGs were recorded, and the Hamilton Rating Scale for Anxiety and the state anxiety scale of Spielberger’s State-Trait Anxiety Inventory were evaluated once a week in 28 patients with generalized anxiety disorder. The Taylor Manifest Anxiety Scale and the trait anxiety scale of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 15 publications
2
26
1
Order By: Relevance
“…This increase was accompanied by a significant reduction in theta activity over the entire cortex. These findings are consistent with those of previous studies, which reported an increase in theta activity in patients with anxiety disorders while experiencing feelings of relaxation [12] In simultaneous EEG-fMRI studies slow EEG patterns were found to correlate negatively with functional connectivity in the default mode network (DMN) during resting state [13]. Reduced delta and increased beta power was positively correlated to increased functional connectivity [14].…”
Section: Discussionsupporting
confidence: 91%
“…This increase was accompanied by a significant reduction in theta activity over the entire cortex. These findings are consistent with those of previous studies, which reported an increase in theta activity in patients with anxiety disorders while experiencing feelings of relaxation [12] In simultaneous EEG-fMRI studies slow EEG patterns were found to correlate negatively with functional connectivity in the default mode network (DMN) during resting state [13]. Reduced delta and increased beta power was positively correlated to increased functional connectivity [14].…”
Section: Discussionsupporting
confidence: 91%
“…Human theta rhythm associated with anxiety has traditionally been recorded in patients performing mental activities without movement in a novel environment (Mizuki et al, 1989;Suetsugi et al, 2000). To recapitulate this behavioral condition as closely as possible, we chose the novel-environment model, which induces alert-immobility states and evokes anxiety, among several conditions known to generate cholinergic theta rhythm in mice (see Materials and Methods).…”
Section: Restoration Of Normal Cholinergic Theta Rhythms In Plc-␤4mentioning
confidence: 99%
“…Anxiety disorders lead to profound suffering and disability that can markedly disrupt family life as well as the life of the sufferer, especially when associated with avoidance behavior and agoraphobia (Gray and McNaughton, 2000;Nutt, 2005;Kim et al, 2010). Although attenuated theta rhythms have been observed in human subjects with increased anxiety (Mizuki et al, 1989;Suetsugi et al, 2000), this phenomenon has not been replicated in animal models of anxiety disorders (Mitchell et al, 2008). Instead, in rodent models of anxiety, it has been shown that (1) GABAergic and serotonergic anxiolytic drugs reduced the frequency of hippocampal theta rhythms elicited by brainstem stimulation (McNaughton et al, 2007), whereas cholinergic drugs did not (Kinney et al, 1999); and (2) increased hippocampal theta rhythms, generated during locomotion in the serotonergic receptor 5HT 1A knock-out mice, showed a positive correlation with an increased anxiety level (Gordon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to identify such a marker, the deficiency of theta activity seen in the EEGs of generalized anxiety disorder patients was modeled in animals (47). The origin of cholinergic neurons, the medial septum, was targeted, because of its role both in the generation of the theta rhythms and in the development of anxiety.…”
Section: Alexander Et Al (2010) Investigated the Effect Of P11mentioning
confidence: 99%